Teacher Education in Greenland - Demant-Poort, Lars; Elstad, Eyvind (Springer International Publishing, 2023)
Abstract Greenland, the world’s largest island, has more than 50 settlements and towns scattered along the coastline, from Siorapaluk in the very north to Aappilatoq more than 2.100 km further south. The vast distances between settlements pose logistical challenges for both schools and for teacher education. Greenland has immense social problems; many children grow up in homes with alcoholism, abuse and violence. The cultural distance between pupils and schooling is often also an issue. Many school-related challenges concern schools’ management, and teachers’ competencies. Teacher shortage, especially in smaller settlements, is a significant problem. Furthermore, teachers are expected to teach a variety of subjects that they are not trained to teach. On top of the challenges to primary and lower secondary schooling, there is a lack of Greenlandic teachers at the higher secondary school level, caused by the unavailability of sufficiently educated teachers from Greenland. Moreover, teacher education faces challenges in creating the conditions needed for interaction between theory and practice. The country has a colonial past but attained self-rule status in 2009. The purpose of this chapter is to explore the evolution of Greenlandic education and further explore the development of Greenlandic teacher education and its challenges.